Modelling Electric and Elastic Properties of Cartilage - Gałka, A.; Telega, J.J.; Wojnar, R. (Engineering Transactions, 2001)
The aim of the paper is to propose a novel approach to modelling the macroscopic electromechanical behaviour of cartilage within the framework of linear response. The cartilage is treated as multiphase material with four constituents: anions, cations, viscous fluid and piezoelectric skeleton. The macroscopic equations were derived by using homogenization methods. Only stationary flow was studied. The elastic macroscopic moduli were determined by assuming, after BFLOOM [60], the honeycomb microstructure of the cartilage. Mathematical developments are preceded by a review of structure and properties of a cartilage.